The Rights to Welfare from Pancasila Perspective for Sea Tribe of Lingga Regency - Tan, Winsherly; Shahrullah, Rina Shahriyani; Agustini, Shenti (Universitas Medan Area, 2023)
Welfare constitutes a goal of the Indonesian State as mandated in the 1945 Constitution. The concept of welfare in Indonesia must be in accordance with Pancasila as the ideology of the Indonesian state. The purpose of this study is to analyze the concept of welfare from the Pancasila perspectives and its manifestation in the Sea Tribe community in Lingga Regency. The method in this study is empirical research with socio-legal approaches. The results of the study show that the welfare based on the Pancasila perspectives is the fulfillment of the rights of society, namely the rights to health, education, housing and adequate income. The realization of this right remains to be a challenge for the Sea Tribe in Lingga Regency, even though the local government has taken adequate regulatory measures by establishing a regional regulation regarding the empowerment of the Sea Tribe community. Therefore, contextual and concretes measures are needed through the integration of work programs in the education, health and social sectors. Public participation is also needed in supporting the government program.